VIDEO MUSIK DAN SIGNIFIKASI TUBUH (Studi Semiotik Godai Aku Lagi Agnes Monica) - Muhammad Ridhlo Al Qodri Sri Utomo (Institut Seni Indonesia Yogyakarta, 2019)
Abstract.Music videos are an audio-visual media that have to express cultural ideas. It produces cultural concepts by placing, demonstrating, and displaying the bodies of the characters. It also constructs the characteristics of male and female bodies according to a cultural perspective that represent ideological constructions. This article analyzes the gender differences of body signification in the Godai Aku Lagi Agnes Monica’s music video. The author uses a semiotic approach to examine the signification of the male and female bodies in visual texts (images and cinematic codes) which are correlated with verbal texts (song lyrics), which are based on a structural perspective to categorize gender differences. In addition, a mythical analysis was used to uncover the ideological interests of the music video.Keywords: Music Video, Body Signification, Agnes Monica